PEMBUKUAN SEDERHANA UNTUK UMKM (RUMAH LITERASI TAMBAK SOGRA) - Maghfiroh, Siti (Jurnal Pengabdian Bisnis dan Akuntansi, 2024)
Micro, Small and Medium Enterprises (MSMEs) are one of the very strong drivers of the people's economy and make a significant contribution to the Indonesian economy. MSMEs are one form of business that can survive the economic crisis that has occurred in Indonesia and are one of the focuses of the development program initiated by the Indonesian government to continue to develop and advance. In order for MSMEs to develop well, information is needed for managers in making decisions. One form of information that is useful in the decision-making process by the owner or manager is accounting information (Bookkeeping). Therefore, it is necessary to provide training on how to do simple bookkeeping for the Tambak Sogra Literacy House, which is one of the MSMEs in Tambak Sogra..